Development of an LC-MS/MS method to quantitatively analyze escitalopram and its metabolites with application in liver and placenta microsome metabolism - Shen, Yifei; Yao, Bingyi; Guo, Yuanqing; Yang, Yujia; Liang, Chenmeizi; Huang, Junze; Zhang, Yuanjin; Wang, Xin (Frontiers in Pharmacology, 2025)
BackgroundEscitalopram (SCT), a highly effective and low-risk antidepressant, is widely used in the clinical treatment of depression. It undergoes two N-demethylation steps, producing its primary metabolites, S-demethylcitalopram (S-DCT) and S-didemethylcitalopram (S-DDCT).PurposeThis study aimed to develop and validate an LC-MS/MS method to simultaneously detect SCT, S-DCT, and S-DDCT, and then apply it to study metabolism in different microsomes, comparing SCT metabolism in rat liver microsomes (RLM), human liver microsomes (HLM), and human placenta microsomes (HPM).MethodsThis study developed a reliable LC-MS/MS method for the simultaneous detection of escitalopram and its metabolites in various microsomal systems. The method was fully validated in rat liver microsomes and then was applied into human liver and placenta microsomes. The method was further applied to investigate escitalopram metabolism in different microsomal systems, notably for the first time in human placenta microsomes.ResultsLC-MS/MS method provides high specificity, good stability, and excellent extraction recovery. Both intra-day and inter-day accuracy (% RE) and precision (% RSD) were within ±15%, with no significant matrix effects observed. The metabolic rates of escitalopram and its metabolite levels differed among rat liver, human liver, and human placenta microsomes, likely due to variations in the types and activities of drug-metabolizing enzymes present in these systems.ConclusionA sensitive and reliable LC-MS/MS method was developed and validated for the quantitative analysis of SCT, S-DCT, and S-DDCT in RLM. Subsequently, the method was applied to the study of HLM and HPM. Incubation experiments using these microsomal systems showed that all three types of microsomes, including HPM, could metabolize SCT.